An electrochemical method for monitoring the acidity of water for fuel cell and environmental applications - Gao, Xiangming (2020)
Maintaining energy and water supplies is still a prime global challenge and hydrogen fuels are set to offer a solution to this challenge, as the combination of hydrogen and oxygen as a fuel stock with the generation of pure water as by‐product is extremely attractive. However, ensuring that the water supply is clean and contaminant‐free is key to ensuring that it can be incorporated into the drinking supply. Contaminants from the fuel cell catalysts or breakdown of materials within the fuel cell over its working life will affect the water quality. The measurement of acidity (pH) is an important indicator for understanding water quality. This article reports a calibration‐free, affordable, screen‐printed electrode (SPE) capable of measuring pH within these waters. This device is fabricated by screen printing pH‐insensitive ferrocene, in conjunction with a pH‐active (and redox‐active) alizarin compound. This electrode reveals consistent voltammetric response to both buffered and low‐buffered media with sufficient supporting electrolytes, achieving a working range from pH 2 to 9.5. This approach provides a disposable, reproducible, low‐cost method for pH monitoring in harsh environments, for example in low‐buffered water quality monitoring and the food industry.